1992
DOI: 10.1128/aem.58.3.891-894.1992
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Pyruvate to Acetoin Helps To Maintain pH Homeostasis in Lactobacillus plantarum

Abstract: Pyruvate is the substrate for diacetyl and acetoin synthesis by lactobacilli. Exogenous pyruvate stimulates acetoin production when glucose is present as an energy source. In Lactobacillus plantarum ATCC 8014, the energy derived from glucose via glycolysis generated a constant proton motive force of about-120 mV. At a low external pH, energized cells rapidly transported and accumulated pyruvate but did not do so when they were deenergized by nigericin. When large amounts of pyruvate were transported and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(49 citation statements)
references
References 28 publications
3
45
0
1
Order By: Relevance
“…Utilization of citrate at acidic pH leads to the production of acetate and neutral compounds such as diacetyl, acetoin and 2,3-butylene glycol. This is faster at acidic pH than at neutral pH, and in several studies it is presented as a pH homeostasis and detoxification process [13]. The present study showed that the rate of citrate uptake for different pH values and citrate concentrations should be subject to a regulation at the level of protein-carrier activity rather than at the genetic expression level.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Utilization of citrate at acidic pH leads to the production of acetate and neutral compounds such as diacetyl, acetoin and 2,3-butylene glycol. This is faster at acidic pH than at neutral pH, and in several studies it is presented as a pH homeostasis and detoxification process [13]. The present study showed that the rate of citrate uptake for different pH values and citrate concentrations should be subject to a regulation at the level of protein-carrier activity rather than at the genetic expression level.…”
Section: Discussionmentioning
confidence: 57%
“…[4,6,7]. A similar mechanism was demonstrated for pyruvate uptake in Lactobacillus plantarum [13]. An antiport hci?-acetate' -(acetate arising from citrate) and a proton-consuming reaction in the cytoplasm have been also proposed [14].…”
Section: Discussionmentioning
confidence: 89%
“…The cellular toxicity attributed to pyruvate under acid stress is controversial. While some studies point to a beneficial role for intracellular pyruvate following acidic stress, others have alluded to a more toxic nature for this metabolite (Harvey & Collins, 1963;Tsau et al, 1992;Repizo et al, 2011;Wu et al, 2014). Hence, to test whether intracellular pyruvate affects S. aureus under acidic stress, we challenged the wild-type strain with increasing concentrations of sodium pyruvate in Tryptic Soy broth (TSB) that was acidified to an initial pH of 4.5 and monitored growth at a wavelength of 600 nm (OD 600 ) for 24 h. Because of the weak acid properties of pyruvic acid (pKa5 2.49), this approach not only allows a small percentage (<1%; estimate based on the Henderson-Hasselbalch equation) of extracellular pyruvic acid to diffuse freely into cells and ensure cytoplasmic acidification, but also simultaneously increases the levels of intracellular pyruvate (upon disassociation of pyruvic acid within the cytoplasm) in the acid stressed cells.…”
Section: Resultsmentioning
confidence: 99%
“…reuteri LTH5448 although Figs 1 and 3). Acetoin formation in homofermentative LAB does not contribute to ATP generation but prevents acidification of the growth medium and hence allows more quantitative substrate utilization (Tsau et al 1992;Gaudu et al 2002). The lack of acetoin formation by heterofermentative lactobacilli may indicate that rapid resource utilization and ATP generation allows quantitatively more utilization of substrates and the formation of products that do not acidify the growth substrate.…”
Section: Strainsmentioning
confidence: 99%